Sistem Pendukung Keputusan Penentuan Tunjangan Pegawai Dengan Metode SAW Studi Kasus ( PT Pos Yogyakarta) - Fitriana Rukhiyati (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
At this time, companies need to think about how to improve employee performance in the midst of today's competition. One method that can improve employee performance is to provide allowances to employees. Employee benefits are a form of appreciation or appreciation from the company for employees who are considered worthy by the company. PT Pos Yogyakarta is a company engaged in the logistics delivery service business. In this study a decision support system was built so that it can be used by companies and institutions/agencies in need. Development of a decision support system The employee benefits are implemented using the simple additive weighting (SAW) method. This method was chosen because it determines the weight for each attribute that will select the best alternative from other alternatives, in this case the alternative in question is an employee who is sure to receive a monthly allowance based on predetermined criteria. Based on the test results, the system built can simplify and assist the process of employee benefits and assist the manager of the human resources division (HR) in making decisions to determine employees who deserve benefits in the company.